Combined respiratory training in an individual with C9orf72 amyotrophic lateral sclerosis. Issue 9 (21st August 2018) - Robison, Raele; Tabor‐Gray, Lauren C.; Wymer, James P.; Plowman, Emily K.
Abstract: This case study examined the impact of a respiratory strength training program targeting inspiratory and expiratory musculature in an individual with C9orf72 amyotrophic lateral sclerosis (ALS). The individual tolerated 24 months of respiratory training completed at home, 50 repetitions per day, and 5 days per week. Significant increases in maximum inspiratory pressure (from 71 to 134 centimeters of water), maximum expiratory pressure (from 108 to 197 centimeters of water) and peak cough flow (from 331 to 655 Liters per minute) were noted and forced vital capacity remained unchanged. A moderate intensity respiratory strength training program applied early in the disease progression improved function in this C9orf72 ALS individual.